A new acetylated spirostanol saponin and other constituents from the rhizomes of Dioscorea althaeoides R. Knuth (Dioscoreaceae). (April 2016) - Li, Xuejiao; Jing, Songsong; Man, Shuli; Li, Xia; Zhao, Chengcheng; Wang, Ying; Gao, Wenyuan
Abstract: A new acetylated spirostanol saponin (7 ), dioscin-6′- O -acetate, was isolated from the rhizomes of Dioscorea althaeoides R. Knuth (Dioscoreaceae), together with fourteen known compounds, including three spirostanol saponins (1 –2, 6 ), three furostanol saponins (10 –12 ), one diarylheptanoid (3 ), three sterols (4–5, 9 ), three aliphatic acids (8, 13 –14 ) and one aliphatic alkane (15 ). Their structures were established by extensive 1D- and 2D- NMR (DEPT, 1 H– 1 H COSY, HSQC, HMBC and NOESY) experiments in conjunction with IR and HRESI/TOF-MS data, as well as the results of acid hydrolysis. The compounds (3 –8, 10 –15 ) were isolated from this species for the first time. The chemotaxonomic significance of these compounds was also discussed Highlights: A new acetylated spirostanol saponin and 14 known compounds, was isolated. The structure of the new saponin was firstly elucidated. The chemotaxonomic significance of the compounds was discussed.